The Role of the Circardian Clock in the Control of Plant Immunity in Arabidopsis Thaliana - Alhumaydhan, Norah (Université d'Ottawa / University of Ottawa, 2015)
The circadian clock regulates a wide range of biological processes, allowing plants to be prepared for predictable daily diurnal changes in environmental cues such as light and temperature. Recent studies have suggested that the circadian clock may also control plant immunity. The exact nature of the interaction between the circadian clock and plant pathogens remains unknown. Our focus in this study is on the elucidation of the role of the biological clock in plant immunity against the necrotrophic pathogen to Botrytis cinerea. In order to do this we tested the level of susceptibility to B. cinerea in Arabidopsis thaliana wild type and transgenic plants: toc1, cca1/lhy, cca1/toc1, lhy/toc1, cca1/lhy/toc1, GLK1 OE, GLK2 OE, glk1, glk2, and glk1/glk2. We demonstrated that the time of infection plays a role in susceptibility to B. cinerea. Specifically, we found that plants are more susceptible to infection in the subjective morning. We also found that genetic mutations in core clock components or in GLK genes leads to changes in susceptibility to B. cinerea. Our data suggests that clock genes are not solely responsible for plant immune responses to B. cinerea but rather the ways in which the biological clock system regulates outcome pathways. Furthermore, when we entrain the biological clock by changing the photoperiod (day length) in normal earth conditions LD 24h and SD 24h, we observed that short day plants had higher susceptibility to B. cinerea than long day plants. In addition, when we entrain the biological clock in different photoperiods, the LD 30h photoperiod plants displayed similar responses as those in the SD 24h photoperiod. The data indicates that day length is not responsible for the control of plant immunity; it is the ability of light to entrain the biological clock that is important. Together, the data strongly support the conclusion that the circadian clock plays a role in plant defense regulation.
Keywords: Circadian clock; Plant immunity; Botrytis cinerea; Susceptibility; Resistance; CCA1/LHY/TOC1mutants; GLKs mutants